2018
DOI: 10.1177/8756087918768348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acrylonitrile–butadiene–styrene/polyethylene terephthalate blends on dimensional stability, morphological, physical and mechanical properties and after aging at elevated temperature

Abstract: A melt blending method was used to prepare acrylonitrile-butadiene-styrene terpolymer and polyethylene terephthalate blends to develop a new blend which can withstand higher temperatures required especially for automotive or home appliance paint curing processes. Blends were characterized by rheological, thermal and mechanical properties. Dimensional stability at 125 C was used to correlate with injection molded part shrinkage. The melt viscosity-composition curves for acrylonitrile-butadiene-styrene/ polyethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…ABS is known as an amorphous polymer, and thus does not have melting temperature [16,22,23]. Therefore, the small endothermic peaks at 220 and 230C) were likely contributed by a chemical additive in the as-received ABS pellet.…”
Section: Resultsmentioning
confidence: 99%
“…ABS is known as an amorphous polymer, and thus does not have melting temperature [16,22,23]. Therefore, the small endothermic peaks at 220 and 230C) were likely contributed by a chemical additive in the as-received ABS pellet.…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradable materials with balanced rigidity (modulus ~1.60 GPa), toughness (impact strength ~40 kJ·m −2 ), and thermal resistance (HDT ~67 °C) are successfully prepared by controlling the properties of polymers at the microscopic level through the concept of heat treatment. Although super-tough PLLA (impact strength > 53 kJ·m −2 or 530 J·m −1 as proposed by Wu) [ 39 ] could not be achieved in this study, the resulting impact is significant to substitute high-impact plastics such as acrylonitrile butadiene styrene (ABS) with the reported impact strengths around 16–21 kJ·m −2 [ 23 , 44 ]. In industry, PLLA and ABS are two of the most common materials used in FDM 3D printing technology.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, poly(lactic acid) (PLA), chitosan, and polybutylene succinate (PBS) have been widely utilized to improve biodegradability of PET due to their good degradability . Many investigations have been reported on physical modification of PET with them via melting blend, such as PET/poly(3‐hydroxybutyrate) composites, PET/PBS composites, PET/PLA composites, and PET/chitosan composites . However, physical blending strategy has been demonstrated that it is not an effective method to address PET pollution issue, because the polymeric chains of PET in these composites are stable during biodegradable process.…”
Section: Introductionmentioning
confidence: 99%